KETERAMPILAN KOMUNIKASI DALAM PEMBELAJARAN PADA GURU PENDIDIKAN SEJARAH - Eka Yuliana Rahman (Program Studi Manajemen Dakwah Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2023)
Communication skills are a specific skill as a result of learning to convey and receive messages effectively, while communication competencies emphasize more on how a person's behavior in communicating is in accordance with their role so as to achieve the expected goals. Competence determines how a person uses the skills they have to achieve success. Someone who is competent in communicating will be able to determine the appropriate pattern of communication in various situations and conditions and be able to adjust his actions accordingly. The teacher is a person who is considered capable of transferring teaching materials, ideas, other insights to students must be seen as a teaching and learning process. But teachers also cannot be anti-criticism, in fact with criticism and suggestions it will add other insights and feedback in learning will be more lively and fun. Communication skills are very necessary to achieve success in learning. With communication skills, students will easily communicate various things related to learning material, both orally and in writing. This research uses a type of research in the form of library research. Literature study is related to theoretical studies and several references that cannot be separated from scientific literature. Teachers are the party most responsible for the ongoing effective communication in the learning process, so teachers as educators are required to have good communication skills in order to produce an effective learning process, in accordance with learning objectives. The era of the 21st century or often referred to as the era of globalization, is marked by the rapid development of science and technology. The development of science and technology brings many changes in human life. These changes can be seen from lifestyle, culture, mindset, life orientation, needs, hopes, so that the mobility of human life runs very fast. Every changing era will bring positive and negative impacts for humans, so that humans must be able to survive in dealing with it. Schools as educational institutions have an important role in preparing the nation's young generation to be able to compete in the era of globalization. The role of the History teacher, especially in schools, is to have control in molding and shaping the young generation of the nation's hope.